Comorbidity Patterns Associated with Renal Dysfunction Across COPD Severity Stages and Clinical Phenotypes - Abdigaffar G. Gadaev; Muborak S. Salaeva; Dinora A. Parpibaeva; Nargiza D. Salimova; Fazilat R. Ismoilova; Abdisalim K. Kulkarayev (International Journal of Medical Science and Dental Health, 2026)
Background: Chronic obstructive pulmonary disease (COPD) is frequently accompanied by cardiovascular, metabolic, haematological and urinary system comorbidities. The presence of renal dysfunction may further modify the clinical profile and prognostic significance of these comorbid conditions. Objective: To comparatively evaluate comorbidities associated with renal dysfunction in patients with COPD across different disease severity stages and clinical phenotypes. Methods: A total of 609 patients with COPD were included in this retrospective study. Patients were analysed according to COPD severity (GOLD stages I–IV) and to the bronchitic, emphysematous and mixed clinical phenotypes. The estimated glomerular filtration rate (eGFR) was calculated with the 2021 CKD-EPI creatinine equation, and renal function was categorised as an eGFR ≤89 versus ≥90 mL/min/1.73 m². The prevalence of ischaemic heart disease, arterial hypertension, diabetes mellitus, anaemia, urinary tract infection and other comorbidities was compared between patients with and without renal dysfunction using Pearson's chi-square test. Results: Renal dysfunction was significantly associated with COPD severity (χ² = 18.79; p < 0.001). In stage III COPD, anaemia (41.6% vs 22.5%, p < 0.05) and urinary tract infection (53.5% vs 22.5%, p < 0.001) were more frequent in patients with an eGFR ≤89 mL/min/1.73 m². In stage IV, ischaemic heart disease (83.6% vs 72.2%, p < 0.01) and anaemia (42.3% vs 25.2%, p < 0.01) were significantly more prevalent. The bronchitic phenotype showed the greatest number of significant comorbidity associations, whereas in the emphysematous phenotype only ischaemic heart disease differed significantly. Conclusion: Reduced renal filtration function in COPD is associated with distinct comorbidity patterns depending on disease severity and clinical phenotype. The strongest associations were observed in advanced COPD and in the bronchitic phenotype, supporting integrated assessment of renal function and major comorbidities in these patients.